Representation of Indonesian women politicians (Media analysis to G30S PKI incident coverage from 1965 to 2015) - Sarwono, Billy (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Background: The G30S/PKI incident that happened in 1965, was known with the murder of six generals by the PKI. The “New Orders” (Orba) regime, Soeharto, did extermination of hundreds of members and supporters of the PKI and imprisoning thousands of people, including Gerwani and those who were not members of PKI or Gerwani because of prejudices and assumptions. Since the reformation era of 1998, many historical facts about G30S/PKI were questioned by the people. During last 50 years the issues of G30S/PKI appeared and sank in the media coverage. Today, the representation of female politicians cannot be separated from the negative memories of the tragedy and the militant image of Gerwani. Methods: The research questions are: How consistent is media reporting when covering the same issue in different political contexts? How does the media, as a means of value socialization, influence the collective memory of society regarding women's activities in politics? The research is conducted using content analysis of a national newspaper from 1965 to 2015 to examine the visibility of Gerwani-related issues over time. Discourse analysis is also used to explore the role and position of Gerwani. Findings: The results indicate that the media tends to side with the dominant group, namely the rulers, and does not voice the interests of weaker groups. Women's interests are framed and represented through the perspective of men. Conclusion: In this context, female politicians receive more appreciation from society when they do not emphasize militant methods in advocating their ideas but instead focus on a caring approach. Novelty/Originality of this Study: The originality of this study lies in its focus on the evolving portrayal of Gerwani over different political eras and its examination of the media's role in shaping collective memory and gender biases. It uniquely integrates collective memory, and feminist perspectives to explore how media representation impacts societal views on women in politics.